Ponsetiho metoda v léčení pes equinovarus congenitus - první zkušenosti - Chomiak, Jiří; Frydrychová, Monika; Ošťádal, Martin; Matějíček, Michal (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2009)
PURPOSE OF THE STUDY To provide a detailed description of the Ponseti method and report the first results of its use, including factors that played a role. MATERIAL AND METHODS In the 2005-2007 period, 91 patients with idiopathic rigid clubfoot (133 feet) were treated by the Ponseti method. The group comprised 62 boys and 29 girls. In most patients the Ponseti method was used as primary treatment, or by 3 months of age when previous treatment failed. In five children this treatment was started between the 3rd and 8th months of age. The result were evaluated by the criteria described by Richards et al., who distinguished four groups. The result was regarded as good when a permanent plantigrade foot was achieved (group 1). Plantigrade feet likely to require posterior release later were considered indeterminate rusults (group 2). Feet that needed posterior release, anterior tibial muscle transfer or lateral column shortening fell in the fair result group (3). Feet requiring complete subtalar release were classified as poor results (group 4). The results achieved in each year were statistically evaluated using Fisher?s test (p<0.05). RESULTS The overall evaluation for 3 years showed good results in 70 %, indeterminate in 7.5 %, fair in 6.76 % and poor in 15.8 % of the treated feet. A detailed analysis for each year revealed that, in 2005, good results (50 %) were recorded in a significantly lower number of feet than in 2006 (72.2 %; p=0.032) and 2007 (93 %; p<0.001). On comparison of the years 2006 and 2007, good results in 2007 were found in a significantly higher number of feet than in 2006 (p=0.019). The poor results were due to 1) very rigid feet (6 %); 2) initial problems with availability of Denis-Brown splints (19 feet; 14.5 %); 3) problems with shoes not made to custom and not fitting patient?s little feet (20 feet; 15 %) 4) faulty techniques of correcting the deformity (4 feet); 5) poor family cooperation in compliance with the bracing protocol (15 feet; 11.2 %). Some of the factors were combined. A delayed beginning of the treatment had no significant effect on the results. DISCUSSION Our 3-year results of clubfoot treatment, by which plantigrade foot position was acheved on average in 77.5 % of the patients, are in agreement with those achieved outside Ponseti centres. However, there were clear differences, with the worst results in 2005. The results comparable with those of Ponseti and his co-workers were achieved by us only in 2007. In accordance with the findings of Richards et al. we suggest that the percentage of short-term good results can change insignificantly within 4 years because of increased recurrence of deformities. CONCLUSIONS Although our initial results were worse than reported in the literature, it can be concluded that the Ponseti method of treating idiopathic clubfoot is more efficient that the methods used previously and can be recommended as an efficient, safe and economical technique. Good compliance with the protocol improves the therapeutic results.
Keywords: Humans; lidé; Female; mužské pohlaví; Infant; pes equinovarus; Male; Physical Therapy Modalities; techniky fyzikální terapie; kojenec; Orthotic Devices; ženské pohlaví; protetické prostředky; Clubfoot